The Effect of the Project-Based Learning Strategy on the Achievement of Art Education Department Students in the Visual Composition Course (Journal of the College of Basic Education, 2025)
The current research seeks to identify the effect of the project-based learning strategy on the achievement of Art Education Department students in the Visual Composition Course. To achieve the objectives of the current research, the researcher adopted a quasi-experimental approach, employing two experimental groups, one receiving instruction using the project-based learning strategy, and the other a control group, one receiving instruction using the lecture method. To implement the experiment, the researcher selected a sample of (60) male and female Art Education Department students receiving the Visual Composition Course. These students were divided equally into two groups: an experimental group and a control group. The researcher ensured that equivalences were achieved before conducting the experiment, as well as constructing an achievement test for the Visual Composition Course, which comprised (30) objective items. The validity and reliability of the test were verified. After implementing the experiment, the research concluded the following:The use of the project-based learning strategy in teaching Visual Composition contributes to raising the level of academic achievement among Art Education Department students.Art education students in the experimental group outperformed those in the control group on the academic achievement test for the visual composition course.